Effectiveness of Autologous Blood and Steroid Injection in Tennis Elbow Based on Visual Analog Score Pain Score and Nirschl Stage - DC, Gopal Sagar (Journal of Nepalgunj Medical College, 2020)
Introduction: Lateral epicondylitis or Tennis elbow is one of the most common causes of lateral elbow pain. Local steroid injection is a time tested treatment for providing symptomatic relief. Local injection of autologous blood in a case of lateral epicondylitis provides pain relief due to its cellular and humoral factor and triggers a healing cascade. Aims: This study aims to compare the outcomes of the autologous blood injection and local corticosteroid injection in the treatment of tennis elbow. Methods: This is a Hospital based study on conducted in the Department of Orthopedics at Nepalgunj Medical College from July 2018 to June 2019. 42 patients with unilateral tennis elbow were divided into two groups-Group A-21 patients (Autologous Blood Injection) and Group B-21 patients (Steroid Injection). Group A received 2 ml of autologous venous blood and mixed with 1 ml of 2% lignocaine solution; Group B patients received 80 mg (in 2 ml) of methyl Prednisolone acetate and 1ml of 2% lignocaine solution. Visual Analogue Scale pain score and Nirschl stage of patients were evaluated before injection and at 2, 6, and 12 weeks of injection were noted and analyzed. Results: Preinjection mean VAS pain score was - 7.48±0.75, 7.52±0.68 in Group A, and Group B respectively while the Nirschl stage was 5.62±0.59 and 5.6±0.5 in group A and B, these scores among two group was not statistically significant. At 2 weeks follow up both groups showed improvement without any significant difference between two groups (p=0.84 and 0.549), while group A had better improvement in VAS pain score at 6 weeks (p=0.001). At 12 weeks follow-up within each group, there was significant VAS pain and Nirschl stage improvement (p=0.001) but there was no significant difference between the two groups. Conclusion: Injection of autologous blood and corticosteroid injection is equally effective in the treatment of Tennis elbow at 12 weeks final follow-up.